Policy Analysis in Efforts to Control and Prevent Forest and Land Fires - Sukainah, Meilin (Asian Journal of Multidisciplinary Research, 2024)
Forest and Land Fires orkarhatula is the event of burning forests and/or land, either naturally or by human action, resulting in losses in several sectors of life, including the sectors of life including Ogan Komering Ilir Regency (OKI). This research aims to analyze efforts to control and prevent Karhula in OKI Regency. OKI Regency. The results showed that the factors that caused forest and land fires in OKI Regency are natural problems and the results of human actions that can occur every year, especially in OKI Regency which there is a lot of peat. So that an effective policy is needed to overcome the problem. This researcher recommends the need for improvement in Karhutla policy, strengthening public awareness, inter-sector coordination and peatland development. peatland development. With the right actions, it is hoped that it can control and prevent forest and land fires in OKI District and surrounding areas.